Influence of Religion on Resolving Social Conflicts: A Multi-Faceted Anal-ysis - Ardhi Khiar; Farid Ahmad Abidin (Insan Akademika Publications, 2024)
: This research examines the influence of religion on resolving social conflict in society. The research employs a multi-faceted methodology, including a comprehensive literature review, in-depth case studies, surveys, and interviews with individuals and communities affected by social conflicts. The findings reveal the complex interplay between religion, conflict, and peace, highlighting the dual nature of religion's influence on conflict resolution. While religion can be a source of division, extremism, and violence, it can also be a powerful force for reconciliation, social cohesion, and peace. Many religious traditions emphasize principles such as compassion, forgiveness, and reconciliation, which can serve as guiding principles for resolving conflicts peacefully. Religious leaders and institutions often play a crucial role in mediating conflicts and promoting dialogue, trust, and cooperation between conflicting parties. Religion is deeply intertwined with social identities, norms, and institutions, and its influence on conflict resolution is shaped by complex interactions between individuals, communities, and broader societal forces. The research concludes by highlighting the importance of continued exploration of the role of religion in conflict resolution and peacebuilding, taking into account the diverse perspectives and experiences of individuals and communities affected by conflicts.